(untitled) (Feni University Journal, 2026)
Despite the theoretical arguments that dividend payments do not add value to shareholders in the absence of taxes and market imperfections, companies still pay dividends to their shareholders, which can influence stock prices. This study investigates the impact of dividend announcements on the stock prices of companies listed under Bangladesh’s CSE-30 index of the Chittagong Stock Exchange. Using a standard event study methodology, the empirical analysis of this study examines the stock price reaction for 44 days surrounding the dividend announcement dates. The paired t-test and correlation analysis results demonstrate that the stock price reaction to dividend announcement is statistically significant. The findings also suggest that dividend announcements convey a message to shareholders, which is reflected in the changes in stock prices. One of the major limitations of this study is its narrow focus on a specific group of financially stable and strong companies listed under the CSE-30 index. Future research may expand the scope to provide a more comprehensive understanding of the impact of dividend announcements on companies’ stock prices in the Bangladeshi stock market. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (131-154)